2012
DOI: 10.1111/j.1460-9568.2012.08226.x
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive patterns of alterations in proton efflux from goldfish retinal horizontal cells monitored with self‐referencing H+‐selective electrodes

Abstract: The H(+) hypothesis of lateral feedback inhibition in the outer retina predicts that depolarizing agents should increase H(+) release from horizontal cells. To test this hypothesis, self-referencing H(+) -selective microelectrodes were used to measure extracellular H(+) fluxes from isolated goldfish horizontal cells. We found a more complex pattern of cellular responses than previously observed from horizontal cells of other species examined using this technique. One class of cells had an initial standing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
(49 reference statements)
1
14
0
Order By: Relevance
“…APs in situ involved a sharp rise in [Ca 2+ ] i , a slow decay, and then a precipitous return to baseline [Ca 2+ ] i , similar to APs of isolated cells in this study and in previous reports (Country et al, 2019; Kreitzer et al, 2012). However, APs in situ were less frequent (median of 1 event per 5 min compared to 7 events per 5 min in Country et al, 2019) and lasted longer (120 s vs. 18 s).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…APs in situ involved a sharp rise in [Ca 2+ ] i , a slow decay, and then a precipitous return to baseline [Ca 2+ ] i , similar to APs of isolated cells in this study and in previous reports (Country et al, 2019; Kreitzer et al, 2012). However, APs in situ were less frequent (median of 1 event per 5 min compared to 7 events per 5 min in Country et al, 2019) and lasted longer (120 s vs. 18 s).…”
Section: Discussionsupporting
confidence: 90%
“…Significant positive correlations were found for AUC (r 2 = .059, p < .01) and duration (r 2 = .043, p < .05); frequency was negatively correlated with r d/s (r 2 = .047, p < .01). No significant correlations were found for amplitude, TTP, or baseline recently, spontaneous, all-or-nothing Ca 2+ transients were found in goldfish in Ca 2+ imaging experiments (Country et al, 2019;Kreitzer et al, 2012). These transients represent APs, and involve Ca 2+ influx into the cytosol via L-type Ca 2+ channels and ryanodine receptors (Country et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…H+-selective microelectrodes were prepared as previously described and used in a self-referencing format to record differential voltage measurements reflective of extracellular H+ flux [ 13 20 ]. To make a self-referencing measurement from isolated cells, the tip of an H+-selective electrode was placed 1–2 μm from the cell membrane and the voltage of the H+-selective electrode recorded; the microelectrode was then moved 30 μm away parallel to the bottom of the dish and a second reading taken; the second reading was subtracted from that obtained close to the cell.…”
Section: Methodsmentioning
confidence: 99%
“…In 1970, Baylor et al demonstrated that turtle retinal horizontal cells contribute a negative feedback signal to the cone photoreceptor light response. When our studies began over 30 years later, the proposed cellular mechanisms of horizontal cell neurotransmission were multiple, controversial, and unconventional: voltage-and sodium-dependent, calciumindependent plasmalemmal γ-aminobutyric acid (GABA) transporter (GAT) activity, as characterized in non-mammalian vertebrates (Schwartz, 2002), ephaptic coupling between photoreceptor calcium channel gating and current flow in horizontal cell glutamate receptors and hemichannels shown in fish retina (Byzov and Shura-Bura, 1986;Kamermans et al, 2001), and photoreceptor calcium current regulation by synaptic cleft pH (Hirasawa and Kaneko, 2003;Vessey et al, 2005;Cadetti and Thoreson, 2006;Kreitzer et al, 2012;Wang et al, 2014;Kramer and Davenport, 2015;Tchernookova et al, 2018;Grove et al, 2019). The apparent lack of the cone surround response block by GABAergic pharmacological agents in turtle, goldfish, mouse, and primate retinas (Thoreson and Burkhardt, 1990;Verweij et al, 1996Verweij et al, , 2003Endeman et al, 2012;Kemmler et al, 2014) was used to argue against a direct role for GABA in feedback inhibition.…”
Section: Introductionmentioning
confidence: 99%